2016
DOI: 10.1111/jnc.13534
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum miR‐93, miR‐191, and miR‐499 are noninvasive biomarkers for the presence and progression of traumatic brain injury

Abstract: The levels of miR-93, miR-191, and miR-499 have been reported to be up-regulated in the tissues of experimental traumatic brain injury (TBI) rat models. However, the clinical diagnostic and prognostic values of the serum signatures of these 3 miRNAs in TBI remain unclear. The purpose of this study was to determine the expression levels of these 3 microRNAs (miRNAs) in the sera of TBI patients and to evaluate their relationships with the severity and clinical outcome of TBI. The serum levels of these miRNAs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 42 publications
0
76
0
Order By: Relevance
“…24 In the same publication, it was hypothesized that this increase could be due to active or passive miRNA release by injured brain tissue. 24 In the same publication, it was hypothesized that this increase could be due to active or passive miRNA release by injured brain tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 In the same publication, it was hypothesized that this increase could be due to active or passive miRNA release by injured brain tissue. 24 In the same publication, it was hypothesized that this increase could be due to active or passive miRNA release by injured brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increased levels of miR-191 have been reported in serum of patients with traumatic brain injury. 24 In the same publication, it was hypothesized that this increase could be due to active or passive miRNA release by injured brain tissue. Therefore, increased levels of miR-191 in blood of patients with MS may reflect release of the miRNAs due to apoptosis of neuronal as well as immune cells.…”
Section: Ta B L E 3 Circulating Mirnas Expression Levels In Female Anmentioning
confidence: 99%
“…Several studies also reported that miR-191-5p may be of value as a prognostic and predictive biomarker in certain tumors, including breast cancer (44), osteosarcoma (45), and head and neck squamous cell carcinoma (46). Furthermore, miR-191-5p was suggested to be a potentially non-neoplastic biomarker to diagnose traumatic brain injury and predict the patient prognosis (47).…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, miR-92a and miR-16 were able to specifically identify patients with mTBI from healthy controls with AUC values of 0.78 and 0.82, respectively (Redell et al, 2010). In addition, miR-93, miR-191, and miR-499 successfully distinguished mTBI patients from healthy controls with AUC values of 1.00, 0.74, and 0.82, respectively (Yang et al, 2016). Taken together, while the biological significance of miRNAs warrants further investigation, data obtained from the studies above suggest that serum miRNA levels may have diagnostic value in TBI.…”
Section: Emerging Blood Biomarkers For Tbimentioning
confidence: 99%